Ins and outs of the cultural polis: Informality, culture and governance in the global South. (February 2019) - Mbaye, Jenny; Dinardi, Cecilia
This article provides an epistemological critique of informality by focusing on cultural governance in two cities of the global South, Rio de Janeiro, Brazil, and Dakar, Senegal. Aiming to enrich debates about urban creativity and urban cultural policy, which are still mainly focused on and articulated from the global North, we consider the broad field of 'informality' research as an entry point for such a discussion. Using case studies from African and Latin American contexts, we focus on the interstices of cultural policy and the borderlands of (in)formality, examining how governmental institutions are entangled in informal processes, and how grassroots cultural interventions become part of mainstream cultural circuits. The analysis sheds light on how these creative spaces of cultural production, located in Southern contexts of urban extremes, contribute to the vitality of informal urbanisms and unsettle predominant views that see them merely as sites of infrastructural poverty and social exclusion. The article suggests that a creative remapping of informality, through an inquiry of the 'ins' and 'outs' of the cultural polis, could improve our translating capacity of academic discourse into institutional/policy-related operations.